How have digital technologies facilitated supply chain resilience in the COVID-19 pandemic? An exploratory case study - Birkel, Hendrik; Hohenstein, Nils Ole; Hähner, Sven (Computers & Industrial Engineering, 2023)
Supply chain resilience (SCRES) is key to preparing for, responding to, and recovering from exceptional disruptions. The purpose of this paper is to explore how the rapid advancement and deployment of digital technologies contributed to SCRES by facilitating effective responses and adaptation to the disruption caused by the COVID-19 pandemic. We begin this paper with an extensive literature review, followed by an exploratory multiple-case study of 12 internationally operating companies. We apply organizational information processing theory (OIPT) as a theoretical lens to provide valuable theoretical insights and implications for management. Our main argument is that low levels of digital maturity and digital technology usage limited the effectiveness and efficiency of SCRES by reducing the capabilities of actors (e.g., visibility, collaboration, agility) to deal with the COVID-19 pandemic. In line with the OIPT, we postulate that SCRES capabilities are positively influenced in the response and recovery phases, increasing visibility and flexibility. Moreover, deploying digital tools in the mid and long run enhances SCRES by enabling organizations to adapt to the “new normal” and prepare better for the next sudden external shock. This study is one of the first to provide in-depth empirical insights through the OIPT lens into how digital technologies helped strengthen SCRES during and beyond the acute phases of the COVID-19 pandemic.
CRIS-Team Scopus Importer:2023-09-08
Keywords: COVID-19; Digital supply chain; Digitalization; Organizational information processing theory; Pandemic; Supply chain disruption; Supply chain resilience; Technology